2001
DOI: 10.1248/jhs.47.346
|View full text |Cite
|
Sign up to set email alerts
|

Production and Application of Monoclonal Antibodies to Human Selenoprotein P.

Abstract: Selenoprotein P is a selenium-rich extracellular protein and is the major selenoprotein in plasma. Although the biological function of selenoprotein P has not been established, we have recently shown that selenoprotein P has phospholipid hydroperoxide glutathione peroxidase-like activity. To study the structure and function of selenoprotein P, we produced monoclonal antibodies against human selenoprotein P. Immunization of rats with purified selenoprotein P was followed by hybridization, cloning, and the estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…It has been reported that these seleniumcontaining materials are incorporated and can be the cellular source of selenium used for synthesis of selenoprotein (22). SeP, which is a selenium-rich extracellular glycoprotein (11,33,34) that functions as selenium transport protein (22,35,36), was the most effective of the materials tested (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that these seleniumcontaining materials are incorporated and can be the cellular source of selenium used for synthesis of selenoprotein (22). SeP, which is a selenium-rich extracellular glycoprotein (11,33,34) that functions as selenium transport protein (22,35,36), was the most effective of the materials tested (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…1 g of liver and kidney in 9 ml of homogenization buffer (10mM Tris-HCl, pH 7.4, 0.1mM EDTA-2Na, 10M sucrose, and 0.1% peroxide-free Triton X-100) was homogenized on ice with an Ultra-Turrax T8 (IKA-Werke GmbH & Co. KG, Staufen, Germany) at 8000 rpm for 10 s. Homogenates were centrifuged at 3500 g and 4°C for 15 min and the supernatant was used for analysis of SelP concentration. The serum, liver, and kidney SelP concentrations were measured using ELISA, as described previously (Saito et al 2001). The assays were conducted with the commercial kits (Life Sciences Advanced Technologies, Saint Petersburg, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Plasma selenoprotein P (SeP) concentrations were determined using a sandwich ELISA with rat antihuman SeP MABs BD1 and AH5, as described earlier (11). The optical density of the plates was measured at 450 nm using an OPTImax tunable microplate reader (Molecular Devices, Sunnyvale, CA, USA).…”
Section: Se and Selenoprotein Assaysmentioning
confidence: 99%